2017
DOI: 10.1016/j.epsl.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing normal faults have limited control on the rift geometry of the northern North Sea

Abstract: 18Many rifts develop in response to multiphase extension with numerical and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 40 publications
2
61
1
Order By: Relevance
“…Structural measurements were converted from the time to the depth domains using the velocity model of Fazlikhani et al (), with those at deeper levels of the basin converted using interval velocities from Christiansson et al (). Although parts of these surveys have been interpreted in local studies (e.g., Claringbould et al, ; Deng, Fossen, et al, ; Duffy et al, ), this represents one of the first studies to integrate the available data with observations from these local studies to resolve the regional multiphase rift evolution of the whole of the northern North Sea.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural measurements were converted from the time to the depth domains using the velocity model of Fazlikhani et al (), with those at deeper levels of the basin converted using interval velocities from Christiansson et al (). Although parts of these surveys have been interpreted in local studies (e.g., Claringbould et al, ; Deng, Fossen, et al, ; Duffy et al, ), this represents one of the first studies to integrate the available data with observations from these local studies to resolve the regional multiphase rift evolution of the whole of the northern North Sea.…”
Section: Methodsmentioning
confidence: 99%
“…A period of relative tectonic quiescence followed RP1 (Coward et al, ; Ziegler, ), although some faults remained active during this so‐called “interrift” period (Claringbould et al, ; Deng, Fossen, et al, ). Early‐Middle Jurassic thermal doming in the Central North Sea resulted in the erosion and removal of large thicknesses of strata across large parts of the North Sea (Davies et al, ; Quirie et al, ; Underhill & Partington, ).…”
Section: Regional Setting and Evolution Of The North Seamentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis may also help explain why pre‐existing faults that juxtapose similar lithologies on either side of the fault in some other multiphase rifts are not reactivated. For example, in east Shetland Basin, pre‐existing faults that juxtapose sedimentary rocks against sedimentary rocks did not influence later rift geometry (Claringbould et al, ). To our knowledge, the influence of a contrast in rheology between foot‐ and hanging wall rock on the likelihood of fault reactivation is not well understood and forms an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Deng, Gawthorpe, Finch, and Fossen (2017) discuss styles of normal fault reactivation during multiphase rifting and distinguish between upward propagation and vertical linkage (see also Giba, Walsh, & Nicol, 2012;Walsh, Nicol, & Childs, 2002). Claringbould, Bell, Jackson, Gawthorpe, and Odinsen (2017), however, demonstrated that not all multiphase-rifted basins involve reactivation of pre-existing normal faults (see also Lee & Hwang, 1993;Tomasso, Underhill, Hodgkinson, & Young, 2008). In cases where pre-existing structural fabric (faults or shear zones) is not reactivated directly, the presence of crustal heterogeneity may still exert control by influencing the location and reorienting the strike of younger rift faults (Phillips, Jackson, Bell, Duffy, & Fossen, 2016;Rotevatn, Kristensen, et al, 2018).…”
mentioning
confidence: 99%